Failure analysis of a steam-water boiler. (November 2020) - Ren, Facai; Hou, Shaoyi; Si, Jun
Abstract: The explosion failure reason of a steam-water boiler was analyzed through macro analysis and theoretical calculation. The results show that the overpressure operation of the boiler is the main cause of the explosion accident.